Applications of artificial intelligence to structure determination of organic compounds. XX*. Determination of groups attached to the skeleton of natural products using 13C nuclear magnetic resonance spectroscopy. Issue 3 (1997) - Rodrigues Rodrigues, Gilberto do V. Gilberto do V.; Campos Campos, Ivan P. de Arruda Ivan P. de Arruda; Emerenciano Emerenciano, Vicente de P. Vicente de P.
Abstract : A procedure for the identification of substituent groups (viz. angelate, tiglate, etc.) attached to any of the atoms in the conventional skeleton of a natural product is described. It consists in the use of the program MACRONO, which was developed for finding subspectra due to the carbons in the said substituent groups amid the raw 13 C NMR spectroscopic data from any given natural product (by means of comparisons of all possible subsets of the observed chemical shifts with those contained in an apposite database, built with literature 13 C NMR spectroscopic data regarding those groups). This procedure enables one to expunge the chemical shifts not due to skeletal carbons from the initial dataset, which then can be input to the expert system SISTEMAT, for skeletal identification.